Produção de etanol anidro por destilação extrativa utilizando soluções salinas e glicerol - Matugi, Karina (2013)
An alternative of renewable fuel is the anhydrous ethanol from biomass. Its production has to aim the minimum consumption of hydric and energetic resources. The bottleneck of the process is located in the downstream that requires technological development with thermodynamics reasoning. This master s degree seeks to address this aspect by studying the dehydration of ethanol by extractive distillation making use of liquid solvent glycerol, salts of potassium acetate and calcium chloride, or both kinds of resources. These resources, called separation agents, can "break" the barrier of azeotropy and have advantages such as no top product contamination and lower energy consumption. The rectification column plus the conventional dehydration system are replaced by a single extractive distillation column which is itself the rectification column, adding the separating agents in the reflux stream. The simulation is performed in steady state using a rigorous model for calculating the column. For non-electrolytic systems UNIFAC model was used, and for systems involving electrolytes UNIFAC model with the addition of the Debye-Hückel term and UNIFAC-Dortmund model. Maximum values for the mean of absolute deviations of temperature and of ethanol molar fraction in vapor phase were 5,51 K and 0,0646 respectively. Though, it was observed that the deviations were higher in the region of least ethanol concentration. The simulation of extractive column with glycerol converged generating anhydrous ethanol following the specification, being a proof of the concept that the application of the proposed process was successful. The simulation of the saline extractive distillation presented difficulties of convergence which will need to be studied in future works.